Double melting behaviour of PA46 matrix composites. (July 2014) - Zhao, N. N.; Zheng, J. W.; Ying, Y.; Jiang, L. Q.; Che, S. L.; Qiao, L.
<x content-type="archive" xml:space="preserve">Abstract</x> Aluminium and alumina were chosen to mix with nylon 46 (PA46) to prepare Al/PA46 and Al2O3/PA46 composites by twin screw extruder. Differential scanning calorimeter, X-ray diffractometer and thermogravimetric analysis were adopted to analyse the melting behaviour of the as received composites. Scanning electron microscope was used to observe the microstructure of the fractural surface of the composites. The results show that two endothermic peaks separately appear at 282 and 289°C in the Al/PA46 and Al2O3/PA46 composites when the temperature rises. The double melting behaviour of the PA46 matrix composites is analysed and discussed by combining the experimental results. It is indicated that this double melting behaviour may be associated with the different crystalline regions in the PA46 matrix formed in the extruding process.